Using video tools to teach nanoparticles characterization: Contents for a distance learning course - Rasteiro, M. G. (2013)
This work deals with the production of multimedia tools for distance learning. Hypermedia provides a non-linear interactive multimedia content which can be used as a pedagogical tool, allowing knowledge discovery in a constructive and pedagogical approach. Hypermedia can include several interactive multimedia contents such as interactive video, text, photos audio, animations or computer graphics, which can be combined among them. In this work the objective is to develop tools for a distance learning course on “Nanoparticles Characterization”. This course will be essentially based on hypermedia contents and can be delivered either in the e-learning or b-learning format. The option was to use interactive videos and, in this manuscript, such a video used for the teaching of nanoparticles characterization using dynamic light scattering will be described. This choice allows the student to choose his own strategy to learn about the measuring technique, since the video is prepared for interaction with the user. This feature is particularly important for lifelong learning courses dedicated to users already in the job market.